Acute Toxicity of Metasystox to Wedge Clam, Donax cuneatus from West Coast - MULEY, D. V.; AKARTE, S. R.; KULKARNI, D. A.; RAO, K. R. (Fishery Technology, 2017)
96 h acute toxicity tests were performed using commerciaI grade metasystox on the marine wedge clam, Donax cuneatus during summer 1985. The behaviour and mortality rates were recorded periodically. Most of the dams responded in opening the shell valves and extending the siphons quicker in low test concentrations (0.004-0.0052 p.p.m) but this was slow and late in high concentrations (0.0056-0.008 p.p.m). Mortality began to occur in 0.008 p.p.m. from 12 h, whereas, in 0.0052 p.p.m. from 60 h onwards. The observed LC0 value was 0.004 p.p.m. and LC50 0.0064 p.p.m. The regression equation established was Y = 79.0891 + 33.4523 X. The rate of oxygen concentration increased at LC0 and LC50 values compared to control indicating the disturbed physiological adjustment. The results are correlated with physico-chemical parameters of seawater and discussed in the light of pesticide toxicity to the dam.